Recurrent patterns in the application of traffic impact analyses: Safety first or last? - Seth LaJeunesse; Jesse D. Saginor; Tabitha S. Combs; Wesley Kumfer; Eric Dumbaugh (Transportation Research Interdisciplinary Perspectives)
Conventional traffic impact analysis (TIA) neglects traffic safety in development review procedures, often serving as an afterthought because the traffic generated is easier to measure than proactively addressing and predicting safety issues. To explore this TIA neglect issue further, interviews conducted with TIA practitioners and developers in five US Mid-Atlantic and Southeast states explore whether and how these professionals incorporated road user safety considerations into their TIA practices. While the means and ends of TIA are quantifiable, understanding the possible role that safety plays in the TIA process requires qualitative analysis. Drawing upon coded interview findings, literature on relationships among traffic congestion, safety, and induced travel demand, qualitative analysis using causal loop diagramming highlights the complex yet fluid interplay between traffic safety and conventional TIA practices through the lens of system archetypes. These practices adhered to two interrelated systems archetypes—generic representations of problem-causing structures that produce established patterns of behavior in a system— discerning potential points to integrate road user safety into TIA practice first as opposed to last in the TIA process. The results enhance TIA practice by explicitly incorporating safety, yet the overall approach is limited in its reliance on the qualitative articulations of TIA practitioners and developers about TIA procedures rather than quantitative analysis of TIA outputs and outcomes.